Investors’ Behavior and Perceptions Towards Stock Market: Structural Equation Modeling Approach - Kinslin, D.; P. Velmurugan, V. (International Journal of Engineering and Technology, 2018)
Investorsâ€™ behavior and perception towards stock indices performances of the stock market was taken into account for this study. Relevant data was collected from 416 equity investors indulged in the stock market situated in diverse parts of southern Tamil Nadu, India. This research focuses on how the investorsâ€™ perceptions regarding stock indices movements of stock markets are affected by their irrational behavior, rational behavior and decision making behavior. In this study SEM approach was applied to analyze the data. The observations from the study disclosed that, the hypothesized model has a good fit and indicates that the anticipated model has the adequate fit, by way of satiating the suggested values. The finding indicates that investors are partly rational and partly irrational because they collect complete financial information and use this information for investment decision making and also use short cuts for decision making.Â